Vasorelaxant and Hypotensive Effects of an Ethanolic Extract of Eulophia macrobulbon and Its Main Compound 1-(4′-Hydroxybenzyl)-4,8-Dimethoxyphenanthrene-2,7-Diol - Wisutthathum, Sutthinee; Chootip, Krongkarn; Martin, Hélène; Ingkaninan, Kornkanok; Temkitthawon, Prapapan; Totoson, Perle; Demougeot, Céline (Frontiers in Pharmacology, 2018)
Background: Ethnopharmacological studies demonstrated the potential for Eulophia species to treat inflammation, cancer, and cardio-metabolic diseases. The aim of the study was to investigate the vasorelaxant effect of ethanolic Eulophia macrobulbon (EM) extract and its main phenanthrene on rat isolated mesenteric artery and to investigate the hypotensive effect of EM. Methods: The vasorelaxant effects of EM extract or phenanthrene and the underlying mechanisms were evaluated on second-order mesenteric arteries from Sprague Dawley rats. In addition, the acute hypotensive effect was evaluated in anesthetized rats infused with cumulative concentrations of the EM extract. Results: Both EM extract (10-4-1 mg/ml) and phenanthrene (10-7-10-4 M) relaxed endothelium-intact arteries, an effect that was partly reduced by endothelium removal (p<0.001). A significant decrease in the relaxant effect of the extract and the phenanthrene was observed with L-NAME and apamin/charybdotoxin in endothelium-intact vessels, and with iberiotoxin in denuded vessels. SNP (sodium nitroprusside)-induced relaxation was significantly enhanced by EM extract and phenanthrene. By contrast, ODQ (1H-[1,2,4]oxadiazolo[4,3,a]quinoxaline-1-one), 4-aminopydidine and glibenclamide (endothelium-denuded vessels) and indomethacin (endothelium-intact vessels) had no effect. In calcium-free solution, both the EM extract and phenanthrene inhibited extracellular Ca2+-induced contraction in high KCl and phenylephrine (PE) pre-contracted rings. They also inhibited the intracellular Ca2+ release sensitive to PE. The acute infusion of EM extract (20 and 70 mg/kg) induced an immediate and transient dose-dependent hypotensive effect. Conclusion: The ethanolic extract of Eulophia macrobulbon (EM) tubers and its main active compound, 1-(4-hydroxybenzyl)-4,8-dimethoxyphenanthrene-2,7-diol (phenanthrene) induced vasorelaxant effects on rat resistance vessels, through pleiotropic effects including endothelium-dependent effects (NOS activation, enhanced EDH production) and endothelium-independent effects (opening of KCa channels, inhibition of Ca2+ channels, inhibition of intracellular Ca2+ release and PDE inhibition).